CASE-CONTROL STUDY: STIGMA’S OF TUBERCULOSIS PATIENT IN BENGKULU CITY, INDONESIA - JIHAN SAMIRA THABIT; KARLINA MAHARDIENI; NOVIANI PRASETYANINGSIH; SURIYANI TAN; JEFRI SUYANTO (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
Background: Negative stigma has the possibility of provoking adverse behaviour. This indicates that people with pulmonary tuberculosis have a diminished likelihood of recovery. Objective: To assess the probability of stigmatisation associated with pulmonary tuberculosis in Bengkulu City. Methods: This research utilises a case-control study design, with simple random sampling as the sampling approach. The ratio of respondents to groups is 1:1. This research was conducted in Bengkulu City, employing a questionnaire as the research instrument. This study utilised two tests: a univariate test and a bivariate test, employing the Stata tool for data analysis. Results: The test outcomes indicated that the majority of respondents in the case group exhibited negative societal stigma towards tuberculosis, inadequate family support, deficient health literacy, low quality of life, and insufficient information. Conversely, most respondents in the control group demonstrated a favourable social stigma towards tuberculosis, possessed robust family support, exhibited great health literacy, maintained a superior quality of life, and displayed substantial knowledge. Conclusion: Mitigating stigma is essential for enhancing early detection and treatment of pulmonary tuberculosis, hence facilitating more successful disease management.